1989
DOI: 10.1016/0042-6989(89)90064-3
|View full text |Cite
|
Sign up to set email alerts
|

Scatter in the metrics of saccades and properties of the collicular motor map

Abstract: Abstract-Saccades, elicited by an identical visual stimulus in repeated trials, exhibit a certain amount of amplitude and direction scatter. The present paper illustrates how this scatter may be used to discern various properties of the subsystem that determines the metrics of a saccade. It is found in humans that scatter along the eccentricity axis is consistently more pronounced than along the direction axis. The ratio of amplitude scatter and direction scatter is approximately constant for all target positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 23 publications
12
70
1
Order By: Relevance
“…Our results confirm many previous findings of isolated aspects of this variability (Jürgens et al, 1981;Becker, 1989;van Opstal and van Gisbergen, 1989;Smeets and Hooge, 2003). One of our new observations is that the variability in movement direction is smaller for purely horizontal and vertical saccades than for saccades in oblique directions.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results confirm many previous findings of isolated aspects of this variability (Jürgens et al, 1981;Becker, 1989;van Opstal and van Gisbergen, 1989;Smeets and Hooge, 2003). One of our new observations is that the variability in movement direction is smaller for purely horizontal and vertical saccades than for saccades in oblique directions.…”
Section: Discussionsupporting
confidence: 82%
“…The confidence ellipses of the endpoints are approximately aligned with the movement direction. In other words, the variability in movement amplitude ( R ) is larger than the variability orthogonal to that ( ), in agreement with the results of van Opstal and van Gisbergen (1989). Endpoint variability increases with target amplitude.…”
Section: Variability In Main Sequence Parameterssupporting
confidence: 81%
See 2 more Smart Citations
“…Previous behavioral experiments conducted under near-optimal conditions (discrete visual targets, exclusion of blatantly errant saccades, elimination of variability caused by initial fixation error) have shown that saccadic endpoints for human subjects exhibit SDs approaching 1°of visual angle at eccentricities similar to those used in our study (van Opstal and van Gisbergen, 1989). Translated into direction around the target ring, this saccade variability alone would lead one to expect a SD in a monkey's direction estimates of ϳ11°.…”
Section: Resultsmentioning
confidence: 80%